Effect of calcium channel blockers on the serum levels of thyroid hormone - Kaur, Rimple J.; Mehta, Bharati; Ambwani, Sneha R.; Gehlot, Anusuya (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The effect of the calcium channel blockers on the cardiovascular system is implemented judiciously in different conditions related to cardiovascular system such as angina pectoris, hypertension, and in cardiac arrhythmias but the aspect that deals with the impact of blockade of calcium channels in other systems like endocrine system remains eclipsed. These effects generally go unnoticed and the present study was formulated to elucidate the serum T3, T4, TSH levels after administration of calcium channel blockers and to observe the resultant side effect on the endocrine glands, if any by this commonly used group of drugs. Methods: The study was conducted on male albino rabbits, they were divided in three groups of ten each and each group received one of the calcium channel blockers- Verapamil, Diltiazem and Nifedipine for three months. At the end of each month the serum T3, T4, TSH levels were evaluated by chemiluminisence. Results:It was found that on continuous daily administration of calcium channel blockers there was a gradual fall in levels of T3 and T4 with rise in TSH levels in comparison to the control value taken before initiating the drug therapy. Conclusion: These findings could have potential clinical implications and this study proposes the importance of blood thyroid hormone level follow up in the long-term calcium channel blocker therapy.